2022
DOI: 10.15376/biores.17.4.6325-6340
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of peak cutting force and cutting energy consumption in cutting of Caragana korshinskii branches

Abstract: Caragana korshinskii (C.K.) flat stubble residue is an abundant biomass energy source in China. Because branch cutting is closely related to the harvesting of forest biomass, it is practical for forestry production and ecological development to investigate the effects of cutting parameters on the peak cutting force and cutting energy consumption of C.K. branches. In this study, the effect of cutting parameters on the peak cutting force and cutting power consumption of branches was investigated by single-factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Based on the analyses of the force distribution along the planes xy and yz and the determined values of the ratios F c /F c and F w /F c , an optimization was carried out [27,40] with the view of seeking the optimum values of the input parameters of the cutting process based on the optimization criteria provided in Table 9. The results of the optimization are provided in Table 10 as a function of the variable weight value for the force F c and the criterion for the ratios F c /F c and F w /F c .…”
Section: Optimization Of the Selection Of Cutting Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analyses of the force distribution along the planes xy and yz and the determined values of the ratios F c /F c and F w /F c , an optimization was carried out [27,40] with the view of seeking the optimum values of the input parameters of the cutting process based on the optimization criteria provided in Table 9. The results of the optimization are provided in Table 10 as a function of the variable weight value for the force F c and the criterion for the ratios F c /F c and F w /F c .…”
Section: Optimization Of the Selection Of Cutting Process Parametersmentioning
confidence: 99%
“…The authors of the cited work carried out an optimization by applying the multi-parameter Box-Behnken test. The determined optimal values were 0.5 m/s for the linear velocity of the blade, 25 • for the blade angle, 20 • for the rake angle, and 1.4 mm for the offset between the blade and the counter-blade [27]. Zhang et al, (2019), in a study of cutting rice stems, demonstrated that selecting an appropriate angle for blade sharpening and the height of the cutting point had a significant effect on energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…This allowed for the determination of the optimal parameter values for this process, that is: knife velocity 0.5 m/s, blade angle 25 • , rake angle 20 • and a distance between the blade and the counter-blade of 1.4 mm. For these parameters the cutting-force value was F = 644.38 N [21].…”
Section: Introductionmentioning
confidence: 99%